2019
DOI: 10.3390/md17080434
|View full text |Cite
|
Sign up to set email alerts
|

Phlorotannins from Undaria pinnatifida Sporophyll: Extraction, Antioxidant, and Anti-Inflammatory Activities

Abstract: Undaria pinnatifida sporophyll (U. pinnatifida) is a major byproduct of U. pinnatifida (a brown algae) processing. Its phenolic constituents, phlorotannins, are of special interest due to their intrinsic ability to precipitate proteins. Herein, a high-temperature extraction procedure was used to isolate these biologically active compounds. The heating temperature, heating time, and extraction solvent (ethanol) concentration were examined with response surface analysis to determine the optimal conditions to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Oddly, higher amounts of extract did not result in higher anti-inflammatory activities (data not shown), which was also verified by Catarino et al [ 57 ] with Fucus vesiculosus phlorotannin-enriched extracts. Contrarily, Dong et al [ 58 ] found that higher doses of U. pinnatifida sporophyll extracts had a higher anti-inflammatory effect. Nonetheless, in this work, extracts show an effective reduction of NO in very low concentrations, showing their potential to be used as an anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…Oddly, higher amounts of extract did not result in higher anti-inflammatory activities (data not shown), which was also verified by Catarino et al [ 57 ] with Fucus vesiculosus phlorotannin-enriched extracts. Contrarily, Dong et al [ 58 ] found that higher doses of U. pinnatifida sporophyll extracts had a higher anti-inflammatory effect. Nonetheless, in this work, extracts show an effective reduction of NO in very low concentrations, showing their potential to be used as an anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…It is also necessary to take into account that post-harvesting storage and processing, such as extraction using different solvents (water, organic solvent, water–organic solvent mixtures) can also affect the composition of the obtained algae extract [ 51 ]. These algae species have been intensively studied not only for their anti-hyperlipidaemic activity [ 52 , 53 ], but also for their anti-tumorigenic [ 54 , 55 ], anti-diabetic [ 56 , 57 ], antiviral [ 58 ], anti-inflammatory [ 59 , 60 ], and antioxidant [ 48 , 60 ] capacities, among others.…”
Section: The Anti-hypercholesterolemic Effect Of Brown Algaementioning
confidence: 99%
“…Among these active compounds, polyphenolic phlorotannins, a group of complex molecular assemblages from the polymerization of phloroglucinol [ 2 ], represent a large class of well-characterized brown algae secondary metabolites [ 3 ]. They have been revealed to have a range of diverse biological functions and activities, such as antibacterial [ 4 ], anti-inflammatory [ 5 ], anti-oxidant [ 6 ], antidiabetic [ 7 ], anti-HIV [ 8 ] and anticancer [ 9 , 10 , 11 ] activities. However, phlorotannins are highly sensitive to external factors such as light, pH, heat and oxidative reagents, which limit their applications in food, cosmetic, nutraceutical and pharmaceutical industries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%